1986
DOI: 10.1068/d040419
|View full text |Cite
|
Sign up to set email alerts
|

State and Class in Africa: A Case for Extending Analyses of the Form and Functions of the National State to the Urban Local State

Abstract: Four alternative theoretical approaches to analysing the form of the national state are outlined, their use in studies of African countries noted, and their appropriateness assessed, to provide background for a consideration of the possible utility of the concept of a local state in analysing African urban situations. Instrumentalist views of the national state In Africa are now less widely used than structuralist approaches, and so structuralist approaches have been considered in more detail, A review is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The fortunes of local government in African countries appear to be inextricably tied with the changing levels of financial autonomy (Mawhood, 1983;Rakodi, 1986;Mutizwa-Mangiza, 1986). For the majority of these countries, local financial resources and autonomy have declined after independence.…”
Section: Discussionmentioning
confidence: 99%
“…The fortunes of local government in African countries appear to be inextricably tied with the changing levels of financial autonomy (Mawhood, 1983;Rakodi, 1986;Mutizwa-Mangiza, 1986). For the majority of these countries, local financial resources and autonomy have declined after independence.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the literature from the mid 1950s to the early 1980s on decentralization displays an enormous range and diversity of temporal, topical and geographical scopes (Conyers 1984). In contrast, the literature on political economics has suspected decentralization to be a demeaning exercise to produce cheap labor opportunities in order to strengthen and promote capitalism on the one hand, and to enhance political legitimacy and maintain a predominant social order on the other (Rakodi 1986), often disregarding the rights of individual groups and in particular alienating those who have little power and are perceived as ''physically not whole'', such as persons with disabilities (Thompson 2006). Some authors have tried to describe decentralization as incompatible with the idea of participatory development and uplifting the marginalized, reinforcing local elite capture and raising the potential for conflict by opening new competition for resources among local elites (Kirsten and Mustafa 1995, Litvack et al 1998, Prudhomme 1995.…”
Section: Overview Of Decentralizationmentioning
confidence: 95%
“…The above arguments in favour of decentralization have been characterized as 'manifest' justifications, in the sense that they are the ones used by policy makers themselves to justify the adoption of decentralization policies. In recent political economy-oriented literature (reviewed by Rakodi, 1986 andMutizwa-Mangiza, 1988), it has been suggested that there may be other 'latent' motives behind the adoption of decentralization policies. These motives revolve around the role of the developmentalist state, particularly the following:…”
Section: Decentralized Local Government Some Basic Conceptual Issuesmentioning
confidence: 99%